Comparison of dementia incidence and prevalence between individuals with and without HIV infection in primary care from 2000 to 2016. (1st March 2022) - Lam, Jennifer O.; Lee, Catherine; Gilsanz, Paola; Hou, Craig E.; Leyden, Wendy A.; Satre, Derek D.; Flamm, Jason A.; Towner, William J.; Horberg, Michael A.; Silverberg, Michael J.
Abstract : Objective: To compare dementia incidence and prevalence after age 50 years by HIV status. Design: Observational cohort, 2000–2016. Methods: People with HIV (PWH) on antiretroviral therapy (ART) and demographically similar people without HIV (PWoH), all aged 50 years and older, were identified from Kaiser Permanente healthcare systems in Northern California, Southern California, and Mid-Atlantic States (Maryland, Virginia, Washington DC). Dementia diagnoses were obtained from electronic health records. Incidence and prevalence of dementia, overall and by time period (i.e. 2000–2002, 2003–2004, …, 2015–2016), were calculated using Poisson regression. Trends were examined using Joinpoint regression. Rate ratios were used to compare dementia by HIV status with adjustment for sociodemographics, substance use, and clinical factors. Results: The study included 13 296 PWH and 155 354 PWoH (at baseline: for both, mean age = 54 years, 89% men; for PWH, 80% with HIV RNA <200 copies/ml). From 2000 to 2016, overall incidence of dementia was higher among PWH [adjusted incidence rate ratio (aIRR) = 1.80, 95% confidence interval (CI) = 1.60–2.04]. Dementia incidence decreased among both PWH and PWoH (−8.0 and −3.1% per period, respectively) but remained higher among PWH in the most recent time period, 2015–2016 (aIRR = 1.58, 95% CI = 1.18–2.12). The overall prevalence of dementia from 2000 to 2016 was higher among PWH [adjusted prevalence ratio (aPR) = 1.86, 95% CI = 1.70–2.04] and was also higher among PWH in 2015–2016 (aPR = 1.75, 95% CI = 1.56–1.97). Conclusion: Reductions in dementia incidence are encouraging and may reflect ART improvement, but PWH are still more likely to have dementia than PWoH. Monitoring the burden of dementia among PWH is important as this population ages. Abstract : Supplemental Digital Content is available in the text